Ammonia volatilization from Nitrogen topdressing fertilization in second-crop corn cultivated under two management systems - Santos, César Ferreira; Pinto, Sheila Isabel do Carmo; Silva, Konrad Passos e; Leite, Paulino da Cunha; Vitor, Vagner Aparecido (Revista Agrogeoambiental, 2020)
Controlled-release fertilizers are possible strategies to reduce losses through fertilization and increase nitrogen (N) use efficiency. In this context, this study aimed to evaluate the efficiency of N sources applied to second-crop corn cultivation. The experiment was carried out in a randomized block design in a 2 x 4 factorial scheme. Two cultivation systems (conventional and no-tillage) and four N fertilizers (urea pearls pure, urea+Cu+B, NBPT-treated urea and complex mineral fertilizer) with four replications were studied. Losses of N-NH3 by volatilization were evaluated up to 14 days after corn N fertilization. The data were subjected to analysis of variance and the means were grouped by the Scott-Knott test at 5% probability. Under the conditions in which the study was carried out, it was observed that urea pearls pure was the least efficient N fertilizer in restricting N-NH3 through volatilization losses. The most efficient fertilizer was NBPT-treated urea. Losses of N-NH3 by volatilization in the no-tillage system were higher than in the conventional cultivation system.